Lower Body Temperature Independently Predicts Delayed Cerebral Infarction in the Elderly With Ruptured Intracranial Aneurysm - Lin, Hui; Wang, Haojie; Xu, Yawen; Lin, Zhangya; Kang, Dezhi; Zheng, Shufa; Yao, Peisen (Frontiers in Neurology, 2022)
Purpose: To assess the correlation between admission body temperature and delayed cerebral infarction in elderly patients with ruptured intracranial aneurysm (IA). Methods: Patients with ruptured IA diagnosed between 2012 and 2020 were retrospectively analyzed. Patients were divided into a non-infarction and an infarction group based on the presence of cerebral infarction after treatment. The demographic and clinical information of the patients was gathered. Outcomes at the 3-month follow-up were assessed using the modified Rankin Scale. Correlation between admission body temperature and cerebral infarction was assessed using Spearman's rank correlation coefficient. A receiver operating characteristic (ROC) curve was used to assess the specificity and sensitivity of admission body temperature to predict cerebral infarction. Results: A total of 426 patients (142 men and 284 women) with ruptured IA were enrolled. Elderly patients with cerebral infarction (12.4%) had a lower body temperature at admission (p < 0.001), higher prevalence of hypertension and diabetes (p = 0.051 and p = 0.092, respectively), and higher rate of poor outcomes (p < 0.001). Admission body temperature was independently associated with cerebral infarction (odds ratio [OR] = 5.469, p < 0.001); however, hypertension (OR = 0.542, p = 0.056), diabetes (OR = 0.750, p = 0.465), and aneurysm size (OR = 0.959, p = 0.060) showed no association. An inverse correlation between admission body temperature and the incidence of cerebral infarction was observed (Spearman's r =−0.195, p < 0.001). An admission body temperature of 36.6°C was able to distinguish infarction and non-infarction patients. The area under the ROC curve was 0.669 (specificity, 64.15%; sensitivity, 81.50%; p < 0.001). Conclusions: Lower body temperature at admission (≤36.6°C) is an independent predictor of delayed cerebral infarction in elderly patients who have undergone treatment for ruptured IA. Therefore, it could be a risk factor for adverse outcomes of IA.